NASIONALISME MULTIKULTURAL DALAM PENDIDIKAN MUSIK - Diah Uswatun Nurhayati (Jurnal Pendidikan Seni dan Industri Kreatif, 2020)
Multicultural nationalism is a paradigm or perspective that may affect the aspects of cognitive, affective, and conative behaviour to build and shape students’ characters through the framework of music education. Along with raising aesthetic awareness, the aim of multicultural nationalism in music education is also leading the Indonesian students to be more tolerant and respectful of other cultures in cultural diversity. The Indonesian nation, comprising various cultures, should be able to learn the thoughts on cultural diversity and construct scientific concepts fruitful for the creation of a national education system, particularly the scheme of music education in Indonesia. Conceptual study on this issue concludes that multicultural nationalism in music education is an integrated perspective of cultural diversity to achieve altogether goals in music education.